The impact of commercial advertising on Facebook on the economy of Kurdish satellites in the Kurdistan Region: (Raparin Journal of Humanities (RJH), 2024)
The impact of commercial advertising in Facebook on the economy of Kurdish television channels in the Kurdistan Region is the subject of this study, which is part of a PhD thesis.The aim of this study is to reveal the reality of advertising and other economic resources of the media in Kurdish satellite channels in the Kurdistan Region, and understanding level of knowledge and of these channels to the process of commercial advertising in Facebook and its characteristics. And determine the impact of commercial advertising in Facebook on the rate, price and revenues of advertising in Kurdish satellite channels. And determine the extent to which these channels have taken various measures to address the impact that commercial advertising in Facebook may have on the economy of their channels.This study is descriptive in nature and its approach is to survey the public opinion. As for the study community is the Media cadres of Kurdish satellite channels in the Kurdistan Region. But the sample is the Media cadres of seven Kurdish news and political channels, they are: GK, Rudaw, KNN, NRT, K24, Kurdsat news, Payam.The data collection tools for this study are interviews and questionnaire format which distributed to 70 media personnel who are also those concerned with the economics of Kurdish satellite channels. This study is also benefited from these previous studies.The most important findings of this study are that commercial advertising in Facebook has had a cognitive, emotional and behavioral impacts on the economy of Kurdish satellite channels in the Kurdistan Region. And advertising is just accounts for 25% of these channels' revenue.